2016
DOI: 10.1161/circulationaha.116.021989
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Therapeutic Hypothermia During Out-of-Hospital Cardiac Arrest Using a Rapid Infusion of Cold Saline

Abstract: URL: http://www.clinicaltrials.gov. Unique identifier: NCT01173393.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(131 citation statements)
references
References 23 publications
3
117
0
7
Order By: Relevance
“…The trial showed no difference in the primary outcomes of survival and neurological status at hospital discharge, but detected more episodes of re-arrest (26% vs 21%) and pulmonary edema on first chest x-ray (41% vs 30%) among patients in the prehospital cooling group. A recent RCT from Australia randomized 1198 patients to usual care or prehospital cooling by infusion of up to 2 L of cold saline (mean 1193 ml) initiated during the delivery of CPR [32]. This trial was stopped early due to concerns that TTM management in receiving hospitals had changed following publication of the Nielsen TTM trial [28]; no differences were observed in the primary outcome of survival at hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…The trial showed no difference in the primary outcomes of survival and neurological status at hospital discharge, but detected more episodes of re-arrest (26% vs 21%) and pulmonary edema on first chest x-ray (41% vs 30%) among patients in the prehospital cooling group. A recent RCT from Australia randomized 1198 patients to usual care or prehospital cooling by infusion of up to 2 L of cold saline (mean 1193 ml) initiated during the delivery of CPR [32]. This trial was stopped early due to concerns that TTM management in receiving hospitals had changed following publication of the Nielsen TTM trial [28]; no differences were observed in the primary outcome of survival at hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years there is a greater use of intranasal cooling, although mostly in combination with other methods: the only found studies in which this method is used alone are Castren [24] (without significant difference in mortality) and Belohlavek [31] (without significant differences in neurological prognosis). No significant differences were found either in mortality -RR 1.01 (0.97 -1.04) -nor in neurological prognosis -RR 1.01 (0.75 -1.35) -in the studies that perform intra-CA cooling [30,33,34]. The evaluation of the methodological quality of the studies provides surprising data.…”
Section: Resultsmentioning
confidence: 98%
“…Six studies investigated therapeutic hypothermia (TH) (21)(22)(23)(24)(25)(26), initiated in the post-arrest phase in three of the studies (21)(22)(23), in the intra-arrest phase in two (24,26) and in either phase in one (25). None of these studies reported significant findings in survival to hospital discharge to support or refute therapeutic hypothermia (Figure 1).…”
Section: Application Of Therapeutic Hypothermiamentioning
confidence: 99%